2015
DOI: 10.1111/nan.12183
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in global DNA methylation and hydroxymethylation are not detected in Alzheimer's disease

Abstract: AimsGenetic factors do not seem to account fully for Alzheimer disease (AD) pathogenesis. There is evidence for the contribution of environmental factors, whose effect may be mediated by epigenetic mechanisms. Epigenetics involves the regulation of gene expression independently of DNA sequence and these epigenetic changes are influenced by age and environmental factors, with DNA methylation being one of the best characterized epigenetic mechanisms. The human genome is predominantly methylated on CpG motifs, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 31 publications
5
55
0
Order By: Relevance
“…In this way, 5-hmC methylation could be an epigenetic mechanism participating in disease development, although these outcomes are still under investigation [44,48]. Due to the large presence of 5-hmC in the brain [49], several studies have been conducted in neurological diseases [50,51]. However, our findings are apparently the first to demonstrate the association between obesity features and 5-hmC methylation.…”
Section: Discussionmentioning
confidence: 49%
“…In this way, 5-hmC methylation could be an epigenetic mechanism participating in disease development, although these outcomes are still under investigation [44,48]. Due to the large presence of 5-hmC in the brain [49], several studies have been conducted in neurological diseases [50,51]. However, our findings are apparently the first to demonstrate the association between obesity features and 5-hmC methylation.…”
Section: Discussionmentioning
confidence: 49%
“…A c c e p t e d M a n u s c r i p t 5 gene expression. In AD patients, significant alterations in genome-wide DNA methylation patterns were described; moreover, different methylation levels of specific genes were observed in comparison to controls, although sometimes the direction of regulation was inconsistent between studies [15][16][17][18][19][20][21]. Nevertheless, contrasting results of no correlation with methylation levels were also reported [22,23] and these discrepancies suggest that the issue deserves further investigation.…”
Section: Introductionmentioning
confidence: 69%
“…In AD patients, gene expression control involving altered promoter methylation have been reported both at genome-wide level and in specific genes, supporting the notion that this epigenetic mechanism of regulation plays an important role in the pathophysiological processes of the disease Page 9 of 20 A c c e p t e d M a n u s c r i p t 8 [15][16][17][18][19]21]. However, the direction of increased versus reduced methylation levels shows inconsistencies between studies, both at a global level of methylation (eg.…”
Section: Discussionmentioning
confidence: 97%
“…Elevation in global levels of DNA methylation has been reported in Alzhei­mer’s disease blood [65] but not in other tissue types, such as the entorhinal cortex [66], where a decrease in global hydroxymethylation was previously reported [67]. Studies in ALS have also reported increased global DNA methylation, both in the spinal cord [15] and blood samples [16] of sALS patients, but their results regarding global DNA methylation detectable in blood have been conflicting.…”
Section: Discussionmentioning
confidence: 99%